Development of Android-based "Pete" Educational Game to Improve Elementary School Student Learning Outcomes in Social Science Learning - Nur Hidayah Hanifah; Muhammad Walid; Candra Avista Putri; Laila Nuriya Sinta; Dian Eka Aprilia Fitria Ningrum (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractSocial science has an essential role in training students' abilities to interact and participate in society. However, social science learning has complex material, so many students have difficulty in learning social science material. This research aims to answer these problems, namely by developing an Android-based educational game to improve social studies learning outcomes. This research is a development research using the ADDIE model, i.e. Analysis, Design, Development, Implementation, and Evaluation. Collecting data using observation, interviews, questionnaires, and tests. Qualitative data were analyzed using descriptive analysis techniques, while quantitative data were analyzed using percentage analysis techniques. Based on the validation and trial results, it is stated that this android-based educational game is valid and feasible to use. Android-based educational games are proven to be able to improve student learning outcomes, especially in social science learning. However, some improvements are still being made in accordance with the suggestions and input from the validators and students.Keywords: educational games, android based, social science learning outcomes.Abstrak Ilmu Pengetahuan Sosial (IPS) memiliki peran penting untuk melatih kemampuan peserta didik dalam berinteraksi dan berpartisipasi di masyarakat. Akan tetapi pembelajaran IPS memiliki materi yang kompleks sehingga banyak peserta didik yang mengalami kesulitan dalam mempelajari materi IPS. Penelitan ini bertujuan untuk menjawab permasalahan tersebut, yakni dengan mengembangkan game edukasi berbasis android untuk meningkatkan hasil belajar mata pelajaran IPS. Penelitian ini merupakan penelitian pengembangan dengan model ADDIE, yaitu Analysis, Design, Development, Implementation, dan Evaluation. Pengumpulan data menggunakan observasi, wawancara, angket, dan tes. Data kualiatatif dianalisis dengan menggunakan teknik analisis deskriptif, sedangkan data kuantitatif dianalisis dengan teknis analisis persentase. Berdasarkan hasil validasi dan uji coba produk yang telah dilakukan, dinyatakan bahwa game edukasi berbasis android ini valid dan layak digunakan. Game edukasi berbasis android terbukti dapat meningkatkan hasil belajar siswa, khususnya pada pelajaran IPS. Namun demikian, beberapa perbaikan masih dilakukan sesuai dengan saran dan masukan dari para validator dan siswa.Kata kunci: game edukasi, berbasis android, hasil belajar IPS.